Impacts of agricultural research on poverty: findings of an integrated economic and social analysis - Meinzen-Dick, Ruth S.; Adato, Michelle; Haddad, Lawrence J.; Hazell, Peter B. R. (International Food Policy Research Institute, 2003)
The extent to which agricultural research has reduced poverty has become an increasing concern of policymakers, donors, and researchers. Until recently, poverty reduction was a secondary goal of agricultural research. The primary focus was on increasing food supplies and reducing food prices, a strategy that was successful in substantially increasing the yields of important food staples. When increased productivity is combined with increased agricultural employment, lower food prices, and increased off-farm employment, agricultural research can be credited with significant reductions in rural poverty. This has been the case particularly in Asia and Latin America, where the vast majority of the developing world population and the world’s poor live.3 However, the paths of causality are complex and highly contingent. The benefits do not necessarily materialize for poor people, and some effects can be negative.